Legalitas Penggunaan Mata Uang Kripto Sebagai Alat Pembayaran Pada Era Industri 4.0 - Kusumo, Mukharrom Hadi; Daim, Nuryanto A. (Universitas Wijaya Putra, 2024)
The public has made many changes to the pattern of economic transactions and non-cash currency transactions, indicating the increasing acceptance and preference of the public for online shopping and the formation of an e-commerce ecosystem, so Bank Indonesia will accelerate the issuance of a central bank digital currency. As in the preamble of the 1945 Constitution that the Indonesian nation is an independent nation based on the freedom of life as a nation, as a form of the Government of the State of Indonesia to promote general welfare and educate the nation's life, there needs to be a normative juridical type of research. The policy to regulate cryptocurrencies as legal tender in the country of El Salvador is a new breakthrough in the world of legal development so that the law follows technological developments in Era Industri 4.0. The legality of the Bitcoin crypto currency of the Republic of El Salvador is not much different from the legality of the regulation of the Indonesian Rupiah currency, thus enabling the Indonesian Government to make the Indonesian Rupiah cryptocurrency as a new means of payment in Era Industri 4.0.